The Invisible Sami Population: Regional Public Healthcare in Northern Sweden 1863–1950 - Haglund, Anders; Axelsson, Per (Umeå University Library, 2017)
Medicine and public health provision have often been used as instruments of power that have shaped relations between the colonizer and the colonized. The county councils, established in 1862 as regional self-governing authorities, became (and have remained) the main architects of Swedish public healthcare services. In this paper, we investigate the political praxis in regional public healthcare development in the three northernmost counties of Sweden, during 1863–1950. Our study finds that the “Lapp shall remain Lapp” policy, which dominated Swedish Sami policy at the time, had little if any influence on regional public healthcare politics. During the focal period, there were no public healthcare facilities and virtually no specific policies or directives aimed at improving access to healthcare for the Sami population.